Single and Combination of Therapy Pembrolizumab in Platinum-Resistant Ovarian Cancer: A Systematic Review of Randomized Controlled Trials: A systematic review of randomized controlled trials - Malkan, Muhamad Ibnu (Maliki Interdisciplinary Journal, 2026)
Platinum-resistant ovarian cancer (PROC) remains one of the most challenging gynecologic malignancies, with limited therapeutic options and poor clinical outcomes. The emergence of immune checkpoint inhibitors, particularly pembrolizumab, has introduced new therapeutic possibilities; however, its clinical efficacy in PROC remains inconsistent and incompletely understood. This systematic review aims to evaluate the efficacy and clinical outcomes of pembrolizumab administered as single-agent and combination therapy in patients with platinum-resistant ovarian cancer, with particular emphasis on survival endpoints and biomarker-based patient stratification. A systematic search of major electronic databases was conducted to identify randomized controlled trials assessing pembrolizumab in PROC. Eligible studies were screened based on predefined inclusion and exclusion criteria. Data extraction focused on objective response rate (ORR), progression-free survival (PFS), overall survival (OS), safety profiles, and molecular or immunological biomarkers. Pembrolizumab monotherapy demonstrated limited antitumor activity, characterized by low ORR and modest survival benefits restricted to selected patient subgroups. In contrast, combination therapies incorporating pembrolizumab with chemotherapy, anti-angiogenic agents, or epigenetic modulators consistently showed improved ORR and prolonged PFS. Pembrolizumab exhibits greater clinical potential in platinum-resistant ovarian cancer when used in combination regimens and guided by comprehensive biomarker stratification. Future trials should prioritize optimized combination strategies and multidimensional biomarker approaches to enhance patient selection and therapeutic efficacy.